Effect of Liquid Food Viscosity on the Load Characteristics of Single-Screw Pumps - Vladimir A. Naumov (Техника и технология пищевых производств)
Introduction. Hydraulic calculations of flow parts play an important role in the improvement of modern technological lines. Such calculations do not include the characteristics of pumping units. Single-screw pumps (SSP) pump high-viscosity liquids in modern food production. The research objective was to develop a new engineering method for assessing the effect of the viscosity of non-Newtonian fluids on the load characteristics of SSP in food production. Study objects and methods. The research featured SSP with a hopper and an auger, designed for pumping high-viscosity liquids. The initial data were taken from officially published test results of Atlas W SSP and the study of the rheological properties of confectionery jelly masses. The research involved authentic methods for calculating the load characteristics of SSP based on the effect of the viscosity of pumped liquid. According to the first approximation, the change in the dimensionless load characteristics was similar in different SSP with an increase in the viscosity of the pumped liquid. The dependence of the viscosity on the rotation speed was determined by the Bingham formula. Results and discussion. The test results of the Atlas W SSP confirmed the need to take into account the minimum rotation speed at which liquid pumping begins in the calculations. The specified frequency was directly proportional to the differential pressure for this series. The study revealed approximate load characteristics of the SSP during jelly pumping. While pumping viscous foods, SSP demonstrated poorer performance and bigger power consumption than during pumping water. The supply decreased and the power increased as the temperature went down and the pectin content in confectionery jelly masses rose. Conclusion. The dependences of the flow rate and power consumed on the rotation speed published by the manufacturers of SSP were obtained during tests on water. The present research resulted in a new method to assess the load characteristics of the SSP when pumping high-viscosity liquids in food production. The obtained regression dependences need further refinement and experimental verification. The method can be used to design new technological pipelines.